Preclinical evaluation of safety and immunogenicity of a primary series intranasal COVID-19 vaccine candidate (BBV154) and humoral immunogenicity evaluation of a heterologous prime-boost strategy with COVAXIN (BBV152) - Sunagar, Raju; Prasad, Sai D.; Ella, Raches; Vadrevu, Krishna Mohan (Frontiers in Immunology, 2022)
Most if not all vaccine candidates developed to combat COVID-19 due to SARS-CoV-2 infection are administered parenterally. As SARS-CoV-2 is transmitted through infectious respiratory fluids, vaccine-induced mucosal immunity could provide an important contribution to control this pandemic. ChAd-SARS-CoV-2-S (BBV154), a replication-defective chimpanzee adenovirus (ChAd)-vectored intranasal (IN) COVID-19 vaccine candidate, encodes a prefusion-stabilized version of the SARS-CoV-2 spike protein containing two proline substitutions in the S2 subunit. We performed preclinical evaluations of BBV154 in mice, rats, hamsters and rabbits. Repeated dose toxicity studies presented excellent safety profiles in terms of pathology and biochemical analysis. IN administration of BBV154 elicited robust mucosal and systemic humoral immune responses coupled with Th1 cell-mediated immune responses. BBV154 IN vaccination also elicited potent variant (omicron) cross neutralization antibodies. Assessment of anti-vector (ChAd36) neutralizing antibodies following repeated doses of BBV154 IN administration showed insignificant titers of ChAd36 neutralizing antibodies. However, the immune sera derived from the same animals displayed significantly higher levels of SARS-CoV-2 virus neutralization (p<0.003). We further, evaluated the safety and immunogenicity of heterologous prime-boost vaccination with intramuscular (IM) COVAXIN-prime followed by BBV154 IN administration. COVAXIN priming followed by BBV154 IN-booster showed an acceptable reactogenicity profile comparable to the homologous COVAXIN/COVAXIN or BBV154/BBV154 vaccination model. Heterologous vaccination of COVAXIN-prime and BBV154 booster also elicited superior (p<0.005) and cross variant (omicron) protective immune responses (p<0.013) compared with the homologous COVAXIN/COVAXIN schedule. BBV154 is successfully completed the both homologous and heterologous combination schedules of human phase 3 clinical trials and received the restricted emergency use approval (in those aged above 18 years) from the Drugs Controller General of India (DCGI).